The daily life of higher education professors and their professional identities: a discussion in light of Michel de Certeau and Claude Dubar (Management and Connections Journal, 2026)
The aim of this paper was to discuss the daily life of higher education professors and their professional identities through the theoretical lenses of Michel de Certeau and Claude Dubar. Daily life encompasses individuals’ actions and experiences within their everyday routines — a context in which, despite the constraints imposed by social and cultural norms, people find ways to act creatively. Professional identities refer to the forms of identity that emerge from the relationship between the “I” and the “We,” particularly within the context of paid occupational activities. A narrative literature review was conducted using the Spell database, the Capes Journal Portal, and Google Scholar. Based on the literature reviewed, six analytical categories were identified as common to the ideas of Certeau and Dubar: the centrality of everyday life; the influence of social structures; individual and collective action; resistance and creativity; alterity; and the construction of identity.
Keywords: Everyday Life; Professor; Higher Education; Certeau; Dubar